Household vegetable agro-biodiversity in northern Vietnam requires diversity in seed sources - Nguyen, Phuong Thi; Struik, Paul C.; Swaans, Kees; Pham Thi, Huong Mai; Hoang, Ky The; Nabuuma, Deborah; Stomph, Tjeerd-Jan (Elsevier, 2026)
CONTEXT: Despite increasing interest in agro-biodiversity, there is little research on the role of diversity in seed sources and related seed systems in supporting vegetable diversity. OBJECTIVE: We aimed to analyze drivers of vegetable diversity and of farmers' choice of seed sources. Moreover, we explored how vegetable diversity and the use of seed sources were related. We focused on households of communities in northern Vietnam with large vegetable diversity as a case in point. METHODS: We conducted 51 stakeholder interviews, 13 focus group discussions, and a survey among 409 households in 32 villages in 2 contrasting regions. Vegetable diversity was defined as counts of unique vegetables. Bayesian mixed-effect models were used to elucidate which factors influenced vegetable diversity at household level, and farmers' seed sourcing decisions. RESULTS AND CONCLUSIONS: On average, households grew 8 (range 1–27) vegetables and used 2 (range 1–6) seed sources. Smaller crop land area resulted in less diversity. Growing more vegetables was associated with women having more years of experience in vegetable production and using more seed sources. Self-saved seed was common, but households relied on off-farm sources for seed that was difficult to produce and/or preserve. Intermediaries created intermediate seed systems, thus linking farmers to formal seed systems. SIGNIFICANCE: As households with larger vegetable diversity used more seed sources, integrated seed sector development should strengthen reliability of all current seed sources to maintain vegetable diversity. This includes reliability of intermediaries and information, and enhancing farmers' capacity for and role in producing and preserving their own seed.